2012
DOI: 10.6061/clinics/2012(05)13
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 expression is associated with aggressiveness in differentiated thyroid carcinomas

Abstract: OBJECTIVES:Forkhead box P3 (FoxP3) expression has been observed in human cancer cells but has not yet been reported in thyroid cells. We investigated the prognostic significance of both FoxP3 expression and intratumoral FoxP3+ lymphocyte infiltration in differentiated thyroid carcinoma cells.METHODS:We constructed a tissue microarray with 385 thyroid tissues, including 266 malignant tissues (from 253 papillary thyroid carcinomas and 13 follicular carcinomas), 114 benign lesions, and 5 normal thyroid tissues.RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 36 publications
4
39
1
3
Order By: Relevance
“…Similar to most other types of human cancers, Foxp+ Tregs in either peripheral blood or tumor tissues of human thyroid cancer are increased, compared with blood and tissue samples from normal subjects or those with thyroid nodular goiter (Cunha et al, 2012;French et al, 2010;Gogali et al, 2012;Muller et al, 2010;Szylberg et al, 2014;Yu et al, 2013), which is confirmed in thyroid cancer tissues and matched non-cancer tissues used in this study (Appendix: Supplementary Fig. S1).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar to most other types of human cancers, Foxp+ Tregs in either peripheral blood or tumor tissues of human thyroid cancer are increased, compared with blood and tissue samples from normal subjects or those with thyroid nodular goiter (Cunha et al, 2012;French et al, 2010;Gogali et al, 2012;Muller et al, 2010;Szylberg et al, 2014;Yu et al, 2013), which is confirmed in thyroid cancer tissues and matched non-cancer tissues used in this study (Appendix: Supplementary Fig. S1).…”
Section: Discussionsupporting
confidence: 68%
“…There are several studies showing that the expression of Foxp3+ Tregs is increased in the peripheral blood and/or cancer tissues of PTC, FTC and medullary thyroid carcinoma (MTC) and that the increased levels of Foxp+ Tregs are associated with a more aggressive form of the cancer and/ or poor clinical prognosis (French et al, 2010;Gogali et al, 2012;Muller et al, 2010;Yu et al, 2013). Very limited information is available for the expression of Foxp3 in thyroid cancer cells, as there are only three reports indicating that thyroid cancer cells of PTC and FTC express Foxp3 which is associated with tumor aggressiveness and resistance to radioiodine treatment (Cunha et al, 2012;Szylberg et al, 2014;Ugolini et al, 2014). Although the function of Foxp3 expressed in thyroid cancer cells remains unexplored, the available data seem to suggest a pro-tumor growth role of Foxp3.…”
Section: Introductionmentioning
confidence: 97%
“…Immune surveillance is one of the most basic functions of the immune system; it can identify, destroy, kill or inhibit The theory also provides a way for the early detection of cancer [17]. When patients have not presented any symptoms and their TAAs are at low level, the immune system is able to monitor the presence of TAAs and cause immune responses, producing large amounts of autoantibodies to clear carcinomic antigens.…”
Section: Discussionmentioning
confidence: 98%
“…B7H1 expression was associated with the presence of a mixture of immune cells infiltrating tumor samples including FOXP3C lymphocytes, which we recently demonstrated associated with DTC features of aggressiveness (Cunha et al 2012b). These lymphocytes may provoke a molecular mimicry that enables immune evasion (Hinz et al 2007) and modulates patterns of molecule expression in tumor cells, thus favoring an aggressive phenotype (Merlo et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Each spot is assessed in triplicate and the final value is given by the mean of triplicates, as previously reported (Minot et al 2009, Morari et al 2010. Aiming to perform survival analysis, staining %median was considered negative and staining Omedian was considered positive, as described previously (Cunha et al 2012b).…”
Section: Immunohistochemical Evaluationmentioning
confidence: 99%